2009
DOI: 10.1086/599987
|View full text |Cite
|
Sign up to set email alerts
|

Esterase D Is Essential for Protection ofNeisseria gonorrhoeaeagainst Nitrosative Stress and for Bacterial Growth during Interaction with Cervical Epithelial Cells

Abstract: estD encodes a carboxylic ester hydrolase and is part of the NmlR regulon in Neisseria gonorrhoeae. An estD mutant was found to be susceptible to nitrite and to S-nitrosoglutathione. This mutant was also unable to infect and survive within human cervical epithelial cells, and it showed reduced ability to form a biofilm on these cells. We conclude that esterase D is an integral part of the nitrosative stress defense system of N. gonorrhoeae and that it has potential importance in pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…The P value was Ͻ0.02 for the copA mutant under each condition assayed. against nitrosative stress (20,21). In contrast, biofilm formation in the copA mutant was essentially the same as that of wild-type gonococci, suggesting that copper ions do not enhance nitrosative stress under these conditions.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The P value was Ͻ0.02 for the copA mutant under each condition assayed. against nitrosative stress (20,21). In contrast, biofilm formation in the copA mutant was essentially the same as that of wild-type gonococci, suggesting that copper ions do not enhance nitrosative stress under these conditions.…”
Section: Discussionmentioning
confidence: 85%
“…In earlier publications, we also showed that mutation of estD and trxB resulted in a greatly diminished ability of N. gonorrhoeae to form biofilms both on glass and over THCECs (20,21). Therefore, we evaluated biofilm formation by wild-type 1291 and 1291 copA after 2 days of growth under continuous flow (Table 1; see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations